Implementation of Conditional Death Penalty: Study of Human Rights and Maqashid As-Sharia - Asiyah Jamilah (Jurnal Mahkamah : Kajian Ilmu Hukum dan Hukum Islam, 2026)
Conditional death penalty has become a pivotal issue in the Indonesian criminal justice system following the enactment of the national Criminal Code (KUHP), which repositions the death penalty from a primary punishment to a special alternative (ultimum remedium). This study analyzes the concept of the conditional death penalty in the national KUHP from the perspectives of Human Rights (HAM) and maqashid as-sharia, while evaluating its relevance to the Indonesian legal context. From a HAM perspective, this mechanism compromises between protecting the absolute right to life and maintaining a deterrent effect against extraordinary crimes through a humanistic 10-year probation period. From the maqashid as-sharia perspective, the conditional death penalty directly aligns with hifzh an-nafs (protection of life) and hifzh al-ummah (protection of society). Rather than rushing into execution, it prioritizes the preservation of the convict's life to allow room for sincere repentance (taubah), while simultaneously preventing greater social harm (dar’u al-mafasid) by ensuring justice for victims. This theory is highly relevant to Indonesia's pluralistic legal context, as it bridges Islamic legal values with the constitutional mandate of Pancasila, particularly the principle of "Just and Civilized Humanity." Based on these findings, this study firmly recommends that the government establish a rigorous, transparent, and independent assessment indicator involving psychologists and human rights experts to evaluate the convict's behavioral changes during probation.